Alginate-shelled SPI nanoparticle for encapsulation of resveratrol with enhanced colloidal and chemical stability. (May 2019) - Zhang, Lingtuo; Zhang, Fang; Fang, Yapeng; Wang, Shaoyun
Abstract: Utilization of protein-based nanoparticles encapsulating resveratrol is hampered by their instability against the environmental stress including pH, ionic strength and UV light. In this study, we fabricated a sodium alginate (Alg)-shelled soy protein isolate (SPI) nanoparticle for the encapsulation of resveratrol, abbreviated as RSAN. The aim of this study was to investigate the existence of Alg shell on both colloidal and chemical stabilities of RSAN. RSAN, fabricated at pH 3.5 and 0.25 mg/mL of Alg, is 204.5 ± 12.1 nm in diameter, −36.4 ± 1.2 mV in ζ-potential and 91.9 ± 3.3% in encapsulation efficiency of resveratrol. RSAN exhibited consistent solubility from pH 2.0 to 8.0 and was resistant to precipitation in ionic strength of 400 mM NaCl at various pHs. The protein in RSAN was prevented from digestion in gastric. Only 15% trans-resveratrol in RSAN was isomerized after 30 min UV light exposure, which is approximate 30% less than the non-shelled nanoparticle (RSN). Moreover, the encapsulation of resveratrol did not reduce its antioxidant activity. The findings suggest that this Alg-shelled nanoparticle has a potential in encapsulating hydrophobic bioactive compounds for utilization in functional foods. Graphical abstract: Image 1 Highlights: Sodium alginate shelled soy protein isolate nanoparticles encapsulating resveratrol were fabricated. The shelled structure significantly improved the colloidal stability of the nanoparticles. Trans-resveratrol in the nanoparticles was protected from isomerization against UV. The nanoparticles are promising for encapsulation of resveratrol for food applications.